(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The advent of the digital age has revolutionized the way we create, consume, and distribute information. This rapid technological advancement has also posed significant challenges to the protection of intellectual property rights (IPR). These rights, which safeguard creative works, inventions, and other intangible assets, are now facing unprecedented threats in the digital realm. One of the primary challenges stems from the ease with which digital content can be copied and distributed. A single click can replicate a piece of software, a song, or a movie, making it difficult to control the dissemination of copyrighted material. This ease of replication has led to rampant piracy, depriving creators of their rightful rewards and undermining the economic incentives for innovation. Furthermore, the emergence of new technologies, such as artificial intelligence and machine learning, has blurred the lines between human and machine-generated content. As AI systems become increasingly sophisticated, they can generate creative works that raise complex questions about ownership and copyright. Another significant issue is the globalization of the digital economy. As information flows across borders at lightning speed, it becomes increasingly difficult to enforce IPR laws internationally.